2015
DOI: 10.1186/s12935-015-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Suramin inhibits cell proliferation in ovarian and cervical cancer by downregulating heparanase expression

Abstract: BackgroundAberrant expression of heparanase (Hpa) is associated with apoor prognosis in ovarian and cervical cancer patients. Inhibitors of Hpa can prevent the growth and metastasis of malignant tumor cells, and suramin may be such a compound that has strong anti-proliferative effects on several kinds of cancer cells. We have therefore tested whether the growth inhibiting effect of suramin on ovarian and cervical cancer cells is due to downregulation of Hpa expression.ResultsSuramin at 300–600 μg/ml significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Similarly, suramin also induced a G0/G1 cell cycle block of up to 39% and inhibited S phase up to 98% of the cell population. These findings are similar to those reported by HuaPing Li et al who found inhibition of cell proliferation by suramin in ovarian and cervical cancer by down regulating HPSE expression [ 47 ]. These results are in good correlation with our results showing that HPSE regulated EMT is inhibited by suramin, an HPSE inhibitor.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, suramin also induced a G0/G1 cell cycle block of up to 39% and inhibited S phase up to 98% of the cell population. These findings are similar to those reported by HuaPing Li et al who found inhibition of cell proliferation by suramin in ovarian and cervical cancer by down regulating HPSE expression [ 47 ]. These results are in good correlation with our results showing that HPSE regulated EMT is inhibited by suramin, an HPSE inhibitor.…”
Section: Discussionsupporting
confidence: 92%
“…Suramin is a hexasulfonated naphthylurea compound that is a market-authorized drug used for antiparasitic treatment since 1921. However, suramin possesses miscellaneous phar-macological effects, including antitumor (8,9), anti-inflammation (10), and antivirus activities (11)(12)(13)(14) etc. Suramin was the first documented HIV-1 reverse transcriptase inhibitor tested in clinical experiments; however, the side effects of the systemic drug delivery of this drug over a long-term treatment resulted in the failure of these clinical trials (15).…”
Section: Seminal Amyloid Fibrils Are Made Up Of Naturally Occurring Pmentioning
confidence: 99%
“…Recently, suramin has been demonstrated to be effective in reducing peritoneal fibrosis [ 10 ], chronic renal fibrosis [ 11 ], and the fibrosis of proliferative eye disease [ 12 ]. Also, it was found that suramin could inhibit cell proliferation [ 13 15 ], which implicated that suramin might be useful in prevention of epidural fibrosis through inhibiting the proliferation of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%